Chapter El teatro del Siglo de Oro y su paulatina presencia en la cultura y la literatura teatrales en los países de habla alemana durante los siglos XVII y XVIII - Tietz, Manfred (Studi e saggi, 2020)
The presence of the theatre of the Spanish Siglo de Oro in the theatre and literary culture of Germany (or the German-speaking countries) in the 17th and 18th centuries is a multifaceted one, and was influenced by many factors. We have to take in account that in the second half of the 17th century and in a large part of the 18th century Spain had been a terra incognita for the Germanic world. This long lack of basic knowledge led to a decontextualization of the Golden Age theatre and sometimes to an unconditional enthusiasm that was not based on historical realities. The protagonists of the 'construction' of a 'Spanish national theatre' included Lessing, Herder, Goethe, the Schlegel brothers and the philosopher Schelling, the most prominent German intellectuals of the time. Within this 'construction' Lope de Vega, Rojas Zorrilla and, above all, Calderón de la Barca are the three icons that will guide both the theory and the practice of drama during the 'two most Spanish decades' of German literary history (1790-1810), even reaching - in the secularized world of the classics and the first generation of German Romantics - the 'deification' of Calderón as perfect poet and author of modern tragedies (without paying much attention to his comedias in a stricter sense and without taking account of his autos sacramentales).